The Role of Qur’anic Entrepreneurship Courses in Advancing Entrepreneurial Movement Initiatives among University Students in Indonesia - Wahid, Abd; Nirwana AN, Andri (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2024)
Abstract This study aims to examine the role of Qur’anic-based entrepreneurship courses in advancing entrepreneurial movement initiatives among university students in Indonesia. Employing a qualitative approach with a library research design, the study critically analyzes relevant scholarly literature on entrepreneurship education and Islamic higher education. The findings reveal that Qur’anic entrepreneurship courses play a significant role in cultivating students’ entrepreneurial mindset through the integration of entrepreneurial competencies with Qur’anic ethical values such as honesty, trustworthiness, and accountability. This integrative approach not only enhances students’ entrepreneurial intentions and readiness but also promotes a value-driven and sustainable entrepreneurial orientation. Furthermore, the course contributes to the development of entrepreneurial ecosystems within higher education institutions through business incubation, practice-based projects, and industry collaboration. At a broader level, the implementation of Qur’anic entrepreneurship education holds strategic implications for addressing graduate unemployment and fostering ethically grounded economic growth in Indonesia. Therefore, integrating Qur’anic values into entrepreneurship education represents an innovative and contextually relevant approach to developing adaptive, productive, and ethically responsible human capital. Abstrak Penelitian ini bertujuan untuk menganalisis peran Mata Kuliah Entrepreneurship Al-Qur’an dalam menggalakkan program gerakan kewirausahaan di kalangan mahasiswa di Indonesia. Studi ini menggunakan pendekatan kualitatif dengan desain penelitian kepustakaan yang berfokus pada analisis kritis terhadap literatur ilmiah terkait pendidikan kewirausahaan dan pendidikan Islam. Hasil penelitian menunjukkan bahwa Mata Kuliah Entrepreneurship Al-Qur’an berperan signifikan dalam membentuk entrepreneurial mindset mahasiswa melalui integrasi antara kompetensi kewirausahaan dan nilai-nilai etika Qur’ani seperti kejujuran, amanah, dan tanggung jawab. Pendekatan ini tidak hanya meningkatkan kesiapan dan intensi berwirausaha mahasiswa, tetapi juga mendorong terbentuknya orientasi kewirausahaan yang berbasis nilai dan berkelanjutan. Selain itu, mata kuliah ini berkontribusi terhadap penguatan ekosistem kewirausahaan di perguruan tinggi melalui pengembangan inkubator bisnis, proyek berbasis praktik, serta kolaborasi dengan dunia industri. Dalam konteks yang lebih luas, implementasi Entrepreneurship Al-Qur’an memiliki implikasi strategis dalam mengatasi tantangan pengangguran lulusan serta mendorong pertumbuhan ekonomi berbasis etika di Indonesia. Dengan demikian, integrasi nilai-nilai Qur’ani dalam pendidikan kewirausahaan menjadi pendekatan inovatif yang relevan dalam pengembangan sumber daya manusia yang adaptif, produktif, dan berintegritas.